2014
DOI: 10.1111/pce.12430
|View full text |Cite
|
Sign up to set email alerts
|

Rice responses to rising temperatures – challenges, perspectives and future directions

Abstract: Phenotypic plasticity in overcoming heat stress-induced damage across hot tropical rice-growing regions is predominantly governed by relative humidity. Expression of transpiration cooling, an effective heat-avoiding mechanism, will diminish with the transition from fully flooded paddies to water-saving technologies, such as direct-seeded and aerobic rice cultivation, thus further aggravating stress damage. This change can potentially introduce greater sensitivity to previously unaffected developmental stages s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
175
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(180 citation statements)
references
References 89 publications
(145 reference statements)
4
175
1
Order By: Relevance
“…Third, when accounting for both paddy yield and milling quality, hybrids appear to be economically superior to conventional lines in both total profits and profit margins. Lastly, climate (specifically, exposure to high nighttime temperatures) can reduce HRY, further supporting previous findings (Cooper et al, 2006;Jagadish et al, 2014;Shi et al, 2013Shi et al, , 2015.…”
Section: Resultssupporting
confidence: 86%
“…Third, when accounting for both paddy yield and milling quality, hybrids appear to be economically superior to conventional lines in both total profits and profit margins. Lastly, climate (specifically, exposure to high nighttime temperatures) can reduce HRY, further supporting previous findings (Cooper et al, 2006;Jagadish et al, 2014;Shi et al, 2013Shi et al, , 2015.…”
Section: Resultssupporting
confidence: 86%
“…Rustad et al (2001) conducted a meta-analysis of experimental data from ecosystem warming studies and found that elevated temperatures significantly increased above ground productivity by 19%. In fact, the effects of night temperature are different from that of day temperature (Xia et al, 2014) and produced a relatively greater challenge in estimating global change impact on crop yield and ecosystem functions (Jagadish et al, 2015). Previous studies on night temperatures have focused either on the effects of HNT and LNT alone (Friend, 1981; Seddigh and Jolliff, 1984a,b,c; Koscielniak, 1993; Bertamini et al, 2005) or the mixed effects of night temperatures and CO 2 concentration (Mortensen and Moe, 1992; Volder et al, 2004; Cheng et al, 2008, 2009, 2010), light period (Gimenez and Rumi, 1988; Turner and Ewing, 1988; Lee et al, 1991; Verheul et al, 2007), intensity (Bunce, 1985; Mortensen, 1994; Rapacz, 1998; Flexas and Osmond, 1999; Davies et al, 2002) as well as other environmental factors (Schoppach and Sadok, 2013) and growth regulators (Shah et al, 2011; Mohammed et al, 2013; Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…During this phase, plots sown at 3 km/h had a higher moisture content (plots with lower plants population). Temperatures may affect pollen formation, grain fertility [34], and decrease potential yields by up to 50% [35]. No significant differences were found for plant length.…”
Section: Resultsmentioning
confidence: 90%